Factors affecting social media addiction in university students and the relationship of social media addiction with depression and fear of missing out - Çağlayan, Mustafa Talha; Arslantaş, Hülya (Journal of Dependence, 2023)
Objective: The study was a cross-sectional study to determine the factors affecting social media addiction in university students, relationship between social media addiction and depression, relationship between social media addiction and fear of missing out. Method: The research was conducted with 448 students studying at a university in the West. Data were collected using the questionnaire form,Social Media Addiction Scale-Adult Form(SMAS-AF),Üsküdar Fear of Missing Out Scale (Ü-FOMOS) and Beck Depression Inventory(BDI). Results: The mean SMAS-AF score averages of female students were higher than that of male students, the SADS-AF score decreased as the age increased. Increasing mother’s use of social media, the use of drugs by the students, the increase in the frequency of social media use, increase in social media usage time in a single session, connecting to social media with a smart phone, using social media for sharing increases the SMAS-AF score. There was a weak positive correlation between students’ SMAS-AF scores and BDI scores, a moderately positive correlation between SMAS-AF scores and ÜFOMOS scores. The three strongest factors in the increase of social media addiction are ÜFOMOS score, social media use for more than 3 hours per day and BDI score, respectively. Conclusion: Students have a moderate level of social media addiction. Depression and social media addiction affect each other bilaterally. Likewise, the fear of missing out and social media addiction affect each other bilaterally. It can be suggested that students be informed about the negative consequences of social media addiction and social media literacy, and that public service announcements about addiction should be broadcast on social media.